Location of multinational firms in asymmetric countries - Pontes, José Pedro (2010)
In this paper, the equilibrium location choices of a large number of firms in an economy consisting of two asymmetrically-sized countries are examined in the context of an evolutionary game. The main conclusions of MARKUSEN and VENABLES concerning the existence of multinational firms (i.e. multiplant firms arise if transport costs are high in relation to plant fixed costs and if the countries are close to symmetry in size) are confirmed in an analytically solvable framework. The framework of an evolutionary game allows the exact determination of the proportions of national and multinational firms in mixed equilibria.